Executive Function and Dysregulated Eating Behaviors in Pediatric Obesity. (8th June 2017) - Gowey, Marissa A; Lim, Crystal S; Dutton, Gareth R; Silverstein, Janet H; Dumont-Driscoll, Marilyn C; Janicke, David M
Abstract: Objective: To examine the association between caregiver proxy report of executive function (EF) and dysregulated eating behavior in children with obesity. Methods: Participants were 195 youth with obesity aged 8–17 years, and their legal guardians. Youth height, weight, demographics, depressive symptoms, eating behaviors, and EF were assessed cross-sectionally during a medical visit. Analyses of covariance, adjusted for child age, gender, race/ethnicity, standardized BMI, depressive symptoms, and family income were used to examine differences in youth EF across caregiver and youth self-report of eating behaviors. Results: Youth EF differed significantly by caregiver report of eating behavior but not youth self-report. Post hoc analyses showed that youth with overeating or binge eating had poorer EF than youth without these eating behaviors. Conclusions: Executive dysfunction, as reported by caregivers, in youth with obesity may be associated with dysregulated eating behaviors predictive of poor long-term psychosocial and weight outcomes. Further consideration of EF-specific targets for assessment and intervention in youth with obesity may be warranted.